Longitudinal ART/AutoART data: a retrospective analysis...15th International Conference on Cochlear Implants and Other Implantable Auditory Technologies; 27th Jun 2018 - 30th Jun 2018; Antwerp, Belgium - Lai, W. K.; Psarros, C. (Journal of Hearing Science, 2018)
Introduction: Auditory Nerve Response Telemetry (ART), the ECAP measurement software from Med-El, was integrated into their Maestro clinical programming software after FDA approval in 2007. More recently, in 2017, AutoART was introduced. This study examines the longterm behaviour of ECAP responses measured using ART/ AutoART for the Med-EL family of compatible implants. Intraoperative ECAP responses are measured routinely using ART at SCIC. Corresponding postoperative ECAP data were collected with AutoART, and compared retrospectively. The way the ECAP is measured using ART and AutoART differs slightly. Technical differences aside, intraoperative ART measurements tend to use higher stimulation levels with the sedated patient, whereas AutoART stimulation is limited to subjectively acceptable levels from the awake patients. Method: Due to the differences in the range of stimulation levels between intraoperative and postoperative measurement sessions were made based on the ECAP amplitude growth function. Note that the ECAP response waveform morphology is not captured by this approach. Where appropriate, the ECAP response waveforms from the various sessions were also examined and compared. Data from a total of 113 ears (left 56, right 57) were examined. The duration between the initial measurements and the most recent measurements ranged from as little as just over 2 weeks to 10 years. Results: The majority of the ECAP data showed changes between sessions. At shorter measurement intervals, particularly postoperatively, the ECAP amplitudes tend to be more stable. The results will be discussed in greater detail. Conclusions: In accordance with current literature, measurements of the ECAP were found to vary with time, particularly between intraoperative and postoperative measurements. The general implication is that if the ECAP thresholds were to be used to assist with sound processor programming, the most recent ECAP measurement should be used where possible.